Passing the Test? From Immigrant to Citizen in a Multicultural Country - Winter, Elke (2018)
Almost all Western countries have recently implemented restrictive changes to their citizenship law and engaged in heated debates about what it takes to become “one of us”. This article examines the naturalization process in Canada, a country that derives almost two thirds of its population growth from immigration, and where citizenship uptake is currently in decline. Drawing on interviews with recently naturalized Canadians, I argue that the current naturalization regime fails to deliver on the promise to put “Canadians by choice” at par with “Canadians by birth”. Specifically, the naturalization process constructs social and cultural boundaries at two levels: the new citizens interviewed for this study felt that the naturalization process differentiated them along the lines of class and education more than it discriminated on ethnocultural or racial grounds. A first boundary is thus created between those who have the skills to easily “pass the test” and those who do not. This finding speaks to the strength and appeal of Canada’s multicultural middle-class nation-building project. Nevertheless, the interviewees also highlighted that the naturalization process artificially constructed (some) immigrants as culturally different and inferior. A second boundary is thus constructed to differentiate between “real Canadians” and others. While not representative, the findings of this study suggest that the Canadian state produces differentiated citizenship at the very moment it aims to inculcate loyalty and belonging.